Landscape governance: Engaging stakeholders to confront climate change - Meinzen-Dick, Ruth S.; Zhang, Wei; ElDidi, Hagar; Priyadarshini, Pratiti (International Food Policy Research Institute, 2022)
Confronting climate change requires action at all levels, from the individual to the global. While there are campaigns to change individuals’ behavior and calls for global and national government action, more attention is needed to governance at the landscape level. The natural resources and ecosystem services that meet the material and nonmaterial needs of communities and form the basis of our agrifood systems, as well as the various types of land users and stakeholders with different land ownership and use rights, are intertwined in landscapes. Much of the debate and policymaking around the interconnected challenges to agrifood systems — climate change, biodiversity loss, environmental degradation, and food insecurity — happen at the global and national scales. However, integrated landscape approaches offer great promise for helping countries to meet their Nationally Determined Contributions to greenhouse gas (GHG) emissions reductions by managing resources to reap multiple benefits and balance economic, social, and environmental goals. In the case of climate change, decisions on how and where to reduce GHG emissions and how to adapt in ways that can address other critical goals, including food and livelihood security, must take place at the landscape level. The real outcomes will be determined by the cumulative actions of many local stakeholders within particular landscapes, with differing, but potentially complementary interests that can support sustainable use of resources within their specific environmental, cultural, and socioeconomic contexts. In this chapter we present a framework that highlights the importance of coordinated action and then look in more detail at approaches to strengthening this coordination for integrated landscape approaches, particularly polycentric governance systems and multistakeholder platforms.